Ending AIDS in Johannesburg : An Analysis of the Status and Scale-Up Towards HIV Treatment and Prevention Targets - World Bank Group (World Bank, Washington, DC, 2016)
Johannesburg, one of South Africa’s metropolitan municipalities and one of the 52 health districts has more people living with HIV (PLHIV) than any other city worldwide at ~600,000. This brief provides the key results of a modeling analysis estimating what it would take in terms of programmatic targets and costs for Johannesburg to meet the Fast-Track targets and demonstrate the impact that this would have. The Optima HIV epidemic and resource allocation model was used, distinguishing 26 sub-populations and populated with the available demographic, epidemiological, behavioral, programmatic and financial data. The analysis demonstrated that Johannesburg has rapidly expanded HIV diagnosis and treatment between 2010 and 2015, reaching 267,236 PLHIV with the ART program in 2015. In 2015, an estimated 70 percent knew about their positive status, about 64 percent of diagnosed PLHIV accessed treatment, and about 54 percent of them were known to be virally suppressed. The analysis suggested that the health impact of successfully scaling-up HIV testing, treatment and ART adherence to the 2020 and 2030 Sustainable Development Goals target levels is very large in Johannesburg. The increase in PLHIV on treatment will result in reductions in new HIV infections (an estimated cumulative difference of ~327 thousand infections from 2016-30). It will also results in reductions in HIV-related deaths (a cumulative difference of ~104 thousand deaths from 2016-30).